2015
DOI: 10.2136/sssaj2015.01.0021
|View full text |Cite
|
Sign up to set email alerts
|

Dating Sediment in a Fast Sedimentation Reservoir using Cesium‐137 and Lead‐210

Abstract: More than 10,000 reservoirs have been constructed in agricultural watersheds in the United States since the 1940s to control floods and sediments. Reservoir sedimentation records provide a unique opportunity to retrospectively study the effects of land use changes and climate variations on sediment production if the sediment chronology could be properly determined. The objectives of this study were to: (i) evaluate the applicability of four unsupported 210Pb (210Pbex) models for dating deposited sediments in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Some farmers have converted the highly erosive parts of their crop land to Bermuda grass pastureland (USDA-FSA, 2015). These initiatives reduced sediment loadings by three to five times as compared to the time prior to 1963 (Zhang et al, 2015). Garbrecht, Starks & Moriasi (2008) stated that there was substantial reduction in sediment yield in the Five Mile Creek sub-watershed in the second half of the 20th century mainly due to conversion of cropland to pasture land.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some farmers have converted the highly erosive parts of their crop land to Bermuda grass pastureland (USDA-FSA, 2015). These initiatives reduced sediment loadings by three to five times as compared to the time prior to 1963 (Zhang et al, 2015). Garbrecht, Starks & Moriasi (2008) stated that there was substantial reduction in sediment yield in the Five Mile Creek sub-watershed in the second half of the 20th century mainly due to conversion of cropland to pasture land.…”
Section: Discussionmentioning
confidence: 99%
“…Studies identified sedimentation as one of the water quality issues in the region with the associated ecological and economic impacts (Zhang et al, 2015). As a result, various agricultural BMPs have been implemented in the watershed to abate sediment loading and transport (Becker, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, soil erosion rates predicted by both methods were relatively low, with the maximum erosion rates being 2 Mg ha −1 yr −1 . The low soil erosion rates even for the long and steep slopes indicated that the undisturbed soil under native rangeland vegetation was effective in keeping soil erosion rates low in the past 50 yr. Zhang et al (2015a) estimated soil erosion rates in the Bull Creek watershed between 1957 and 2003 based on the measured sedimentation volume in the reservoir controlling the watershed. The estimated soil erosion rates for the Bull Creek watershed, corrected for a reservoir trapping efficiency of 90% and a sediment delivery ratio of 42%, were 29.0 Mg ha −1 yr −1 during 1957 to 1962 and 6.8 Mg ha −1 yr −1 during 1963 to 2003.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, we based our calculations of the historical SSYs on the C‐CRS dating. In general, the C‐CRS model is more appropriate for dating sediment deposited continuously over periods of <100 years leading up to the time of sampling (Zhang et al, ). As the lifespan of a reservoir is usually <100 years, it can be assumed that the C‐CRS model is especially appropriate for reservoir deposit dating, particularly in the case of temporal variations in the deposition rate.…”
Section: Discussionmentioning
confidence: 99%